High Gain Series Fed Two Dipole Array Antenna with Reduced Size for LTE Application. Issue 2 (4th March 2022) - Haridoss, G.; Ravimaran, S.; William, J.; Wasim, Mohammad; Abdullah, M.
Abstract : A novel series-fed two dipole antenna array with enhanced gain and reduced size is proposed covering the different frequency bands of the LTE communication technology. The proposed antenna works in the frequency range from (1.7–2.8) GHz. Also the gain of the antenna is increased to 1.5–2 dB compared with the conventional and modified STDA. The size of the proposed antenna (Circular patch STDA) is reduced by 25% approximately compared with the conventional STDA and 13% approximately with modified square patch top loading STDA.